Potential natural gas pipe line at Universiti Malaysia Pahang laboratory and residential college unit for future development - Muhammad Arif, Ismail (2010)
The consumption of energy has increased as result of rapid economic growth in Malaysia. Realizing the importance of energy, natural gas can be alternative energy source which is more effective and cheap compared to electricity. The main objective of this project is to design the distribution line of natural gas to all residential college units (UKK) at Universiti Malaysia Pahang (UMP) located at Gambang, Kuantan. UMP is located near to gas service station, approximately 500 m with the existing gas service station in Gambang, it is convenient way to tap the natural gas at future point to UMP. Currently, student’s cafeteria using LPG bulk storage for cooking and it is not continuously supply and can disturb their production. Besides that, student also have water heater in their hostel, thus it will affect the electricity bill for every month. The scope of this project are the consumption of load demand that can accommodate for all residential college unit and student’s cafeteria, network piping calculation using Cox’s equation by calculation of load and determine the classification of polyethylene pipe construction, and lastly using PDMS software to draw the pipeline. The method that been used are to calculate all piping size and gas load demand by using Cox’s equation according to standard such as MS930 and ASME B31.8 to make sure that the piping design is safe for the construction. As the result, the total pressure drop from the source to load consumer is below 15% which is acceptable for designing pipeline. The Medium Density polyethylene (MDPE) pipe is use for distribution line construction. Lastly, the piping sizes for MDPE pipe are 2 inches and 3 inches. As the conclusion, natural gas can reduce about 50% the utilities cost compare to electricity.